Search for a light Z′ in the Lμ−Lτ scenario with the NA64-e experiment at CERN - Andreev Yu. M. Yury Mikhaylovich; Banerjee D.; Chumakov A. G. Aleksandr Grigorjevich; Dusaev R. R. Renat Ramilyevich; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Trifonov A. Yu. Andrey Yurievich; Vasilishin B. I. Bogdan Ivanovich; Voronchikhin I. V. Ilya Vyacheslavovich (2022, 2022)
Title screen